SISTEM PELAPORAN KEUANGAN BADAN USAHA MILIK DESA (BUMDES) PIDOTA DI DESA DADAKITAN - Trisna Trisna; Yuliana Yuliana; Septia Rahayu (Jurnal Ilmiah Hospitality, 2022)
The purpose of this study was to determine the Financial Reporting System of Pidota Village Owned Enterprises (BUMDes) in Dadakitan Village. This type of qualitative research, with data collection techniques in the form of observation, interviews and documentation, data analysis techniques used are descriptive analysis such as data collection, data selection and reduction, data presentation, and drawing conclusions. The results of this study indicate that the Pidota Village-Owned Enterprise Financial Reporting System (BUMDes) in Dadakitan Village is in accordance with or not in accordance with the financial reporting standards set by the Tolitoli Regency Community and Village Empowerment Service, especially those dealing with BUMDes.